2005
DOI: 10.1590/s0103-90162005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro organogenesis in passion fruit (Passiflora edulis f. flavicarpa)

Abstract: In vitro organogenesis of passion fruit was studied by the induction of adventitious buds from leaf discs in culture media supplemented with benzyladenine (BAP) or thidiazuron (TDZ). To minimize adverse effects of ethylene accumulation on shoot development, silver nitrate (AgNO 3 ) was added to the induction media. Both BAP (0; 2.2; 4.4; 6.6 µmol L -1 ) and TDZ (0; 1.1; 2.2; 3.4 µmol L -1) were effective in promoting shoot development. Although no significant differences were detected using AgNO 3 (23.5 µmol L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 23 publications
0
38
0
4
Order By: Relevance
“…The same authors concluded that the use of coconut water help to prolong the sub-culturing time and produced highly robust plants which were more able to survive in greenhouse condition. TREVISAN et al (2005) also demonstrated the advantage of coconut water for stem elongation and plant development in passion fruit. VILLA et al (2010) working with the olive cultivar 'Ascolano 315' reported that 25ml L -1 of coconut water associated with 500µg L -1 of BAP generated plantlets with higher shoot length and heavier fresh biomass than in plantlets cultivated without these compounds.…”
Section: Introductionmentioning
confidence: 89%
“…The same authors concluded that the use of coconut water help to prolong the sub-culturing time and produced highly robust plants which were more able to survive in greenhouse condition. TREVISAN et al (2005) also demonstrated the advantage of coconut water for stem elongation and plant development in passion fruit. VILLA et al (2010) working with the olive cultivar 'Ascolano 315' reported that 25ml L -1 of coconut water associated with 500µg L -1 of BAP generated plantlets with higher shoot length and heavier fresh biomass than in plantlets cultivated without these compounds.…”
Section: Introductionmentioning
confidence: 89%
“…Adventitious shoot production from leaf segment has been previously observed in P. alata (Pinto et al 2010;Rodriguez et al 2007). The use of cytokinins for in vitro organogenesis in Passiflora species has also been reported with induction of adventitious buds in response to BAP alone or in association with NAA, TDZ or kinetin (Becerra et al 2004;Dornelas and Vieira 1994;Hall et al 2000;Trevisan and Mendes 2005). Shoots from root explants of P. cincinnata and P. edulis grown in MS medium with 2.89 uM GA 3 were elongated about 2 cm after 10 days in culture .…”
Section: Resultsmentioning
confidence: 86%
“…Pinto et al (2010) reported that in vitro organogenesis induction of sweet passion fruit occurred more efficiently when hypocotyl segment-derived explants were cultured in MS medium supplemented with BAP and AgNO 3 under 16-h photoperiod. Trevisan et al (2005) also reported that the bud induction and shoot development of P. edulis Sims. F. flavicarpa was enhanced TDZ and AgNO 3 -supplemented media.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In order to minimize the effect of the accumulation of ethylene, in the development of passion fruit shoots, [8] added silver nitrate to the culture media supplemented with benzyladenine (BAP) or thidiazuron (TDZ) and verified that adventitious buds developed in culture media with supplemented AgNO 3 were more vigorous.…”
Section: Resultsmentioning
confidence: 99%